Разробка та дослідження методу індуктивного моделювання з нечіткими вхідними змінними - Pinchuk, D. A. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2017)
A method for group data handling in the case of fuzzy inputs is presented. The solution for the problem of supermarket income forecast is offered. The results are compared with the fuzzy method of group data handling.